Smad5, a tumor suppressor candidate at 5q31.1, is hemizygously lost and not mutated in the retained allele in human leukemia cell line HL60 - Zavadil, J; Brezinová, J; Svoboda, P; Zemanová, Z; Michalová, K (Leukemia, 1997)
Deletions of the long arm of chromosome 5 with common overlapping segment 5q31.1 are among the most frequent cytogenetic aberrations in myelodysplastic syndromes and acute myeloid leukemias (MDS/AML). We have constructed a YAC-based physical map of the 5q31.1 critical locus and localized the transcriptional transactivator Smad5 adjacent to loci showing consistent loss of heterozygosity in these disorders. Smad5 plays a key role along the bone morphogenetic protein-4 (BMP-4) inhibitory signalling pathway inducing embryonic hematopoiesis. Smad5 homologs Smad2 and DPC4 have recently been linked to human cancer. FISH analysis of AML-M2 cell line HL60 and of four MDS/AML patients revealed consistent hemizygous loss of the Smad5 locus. In HL60 cells, a translocation event within 5q31.1 associated with loss of adjacent material leads to disruption of the critical locus with partial retention of the 5q31.1 genomic sequences on a marker chromosome. RT-PCR sequencing analysis of the HL60 Smad5 remaining allele ruled out the functional inactivation of the gene analogous to that occurring in the Smad5 homologs DPC4 and Smad2 in cases of pancreatic and colorectal cancers. Mutational analysis of Smad5 in MDS/AML cases is in progress.
Keywords: Genes, Tumor Suppressor; Alleles; Trans-Activators; trans-aktivátory; HL-60 Cells; RNA, Messenger; Humans; tumor supresorové geny; RNA nádorová; lidské chromozomy, pár 5; Phosphoproteins; Chromosomes, Human, Pair 5; lidé; In Situ Hybridization, Fluorescence; genetické markery; messenger RNA; molekulární sekvence - údaje; Genetic Markers; kosmidy; protein Smad5; Cosmids; DNA vazebné proteiny; Leukemia, Myeloid, Acute; Base Sequence; místa se sekvenční adresou; umělé kvasinkové chromozomy; mapování chromozomů; RNA, Neoplasm; Sequence Tagged Sites; akutní myeloidní leukemie; Smad5 Protein; alely; sekvence nukleotidů; HL-60 buňky; Chromosomes, Artificial, Yeast; hybridizace in situ fluorescenční; fosfoproteiny; Chromosome Aberrations; Chromosome Mapping; Molecular Sequence Data; DNA-Binding Proteins; chromozomální aberace